Vestibular Function in Older Adults With Cognitive Impairment: A Systematic Review. Issue 5 (22nd September 2021) - Bosmans, Joyce; Jorissen, Cathérine; Gilles, Annick; Mertens, Griet; Engelborghs, Sebastiaan; Cras, Patrick; Van Ombergen, Angelique; Van Rompaey, Vincent
Abstract : Supplemental Digital Content is available in the text. Abstract : Importance: Given the rising prevalence of patients with dementia and those at risk for it, early identification is prioritized. As vestibular dysfunction is associated with Alzheimer's disease (AD) and may contribute to its onset, vestibular assessment may yield an opportunity in early dementia screening. Objective: This systematic review structures and compares the different raw outcome measures used to assess vestibular function while comparing older adults with preserved cognition to individuals with cognitive impairment, either suffering from mild cognitive impairment (MCI) or AD. Design: Two investigators independently and systematically searched publications performing objectively measured vestibular testing in a patient population consisting of either MCI or AD, compared with a control group of older adults with preserved cognition. No limitations regarding language or publication date were applied. References of the retrieved articles were hand searched for relevant articles. Results: Seven articles were included for analysis. A total of 235 older adults with impaired cognition (150 AD, 85 MCI) were compared with a control group of 481 older adults with preserved cognition. Evaluation of the peripheral vestibular function included video head impulse test (vHIT), videonystagmography (VNG), electronystagmography (ENG) including bithermal caloric irrigation and vestibular evoked myogenic potentials (VEMP). The VEMP test, assessing otolith function and the elicited vestibulocollic reflex (VCR), was able to differentiate subjects with AD and its prodromal stage from healthy controls, with p13 latency ( p < 0.05) and amplitude ( p < 0.05) having the most discriminating power. No correlation between cognitive decline and vestibulo-ocular reflex measurements in different frequency ranges of the semicircular canals (using vHIT, rotatory chair testing, and caloric irrigation) was found. Because of the limited number of available studies and the large heterogeneity in outcome measures, these results have to be interpreted with caution. Conclusions: Measurements of the VCR, as evoked by the VEMP test, discriminate between patients with cognitive impairment (MCI and AD) and older adults with preserved cognition, whereas measurements of the vestibulo-ocular reflex do not. More studies are needed to further elaborate on these findings.